Evaluasi Kebijakan Pengelolaan Sampah di Kabupaten Demak - Kiki Hardiyanti; Budi Puspo Priyadi (HIGIENE: Jurnal Kesehatan Lingkungan, 2020)
The waste problem in Indonesia is a national problem, and based on the Constitution of the Republic of Indonesia Article 18 Paragraph (6) that local governments have the right to stipulate regional regulations and other regulations to carry out autonomy and co-administration, so that regions have a role to play in alleviating waste problems. in the area. Law Number 23 of 2014 concerning Regional Government Article 11 Paragraph (2), namely mandatory government affairs as referred to in paragraph (1) consists of government affairs related to basic services and government affairs not related to basic services. Then, Article 12 Paragraph (1) point (c) is public works and spatial planning, and Paragraph (1) point (e) is the environment. One area that does not escape experiencing waste problems is Demak Regency. The purpose of this study is to determine how the achievement of waste management policies implemented in Demak Regency. The method used in this research is descriptive qualitative research. The criteria used to assess the evaluation are effectiveness, efficiency, adequacy, responsiveness and accuracy. The results of the writing show that the waste management policy carried out in Demak Regency through the Environmental Service has not been optimal, especially the waste management carried out in the Kalikondang landfill.Keywords: Garbage, Demak Regency, Policy Evaluation, Environmental Service, TPA Kalikondang